2010
DOI: 10.1016/j.neuroscience.2010.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Promoter specific alterations of brain-derived neurotrophic factor mRNA in schizophrenia

Abstract: The brain-derived neurotrophic factor (BDNF) gene contains 4 major 5′ promoters which generate alternate transcripts. Previously, we found that pan-BDNF mRNA and protein is reduced in the dorsolateral prefrontal cortex (DLPFC) from patients with schizophrenia. In this study, we determined which of the 4 most abundant BDNF alternate transcripts (I–IX, II–IX, IV–IX and VI–IX) are altered in schizophrenia. Using a cohort from the NIMH, USA, we found that BDNF II–IX mRNA was significantly reduced in the DLPFC of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 96 publications
1
85
0
Order By: Relevance
“…While this result mirrors the decreased BDNF expression seen in patients, the Val66Met variant associated with psychosis is accompanied by less BDNF methylation in the PFC (Mill et al, 2008). Owing to the brain region-and promoter-specific nature of these effects (Wong et al, 2010), and differences in rodent and human neuroanatomy, more evidence will be required to understand the interaction between Val66Met, BDNF epigenetics, stress, and psychosis (Boulle et al, 2011). Chronic stress also interacts with the cannabinoid system to sensitize the effects of cannabinoids and shift cannabinoidmediated control of plasticity from projection neurons to GABAergic cells (Patel et al, 2009;Reich et al, 2013).…”
Section: Environmental Insults Disrupt Gabaergic System Developmentmentioning
confidence: 68%
“…While this result mirrors the decreased BDNF expression seen in patients, the Val66Met variant associated with psychosis is accompanied by less BDNF methylation in the PFC (Mill et al, 2008). Owing to the brain region-and promoter-specific nature of these effects (Wong et al, 2010), and differences in rodent and human neuroanatomy, more evidence will be required to understand the interaction between Val66Met, BDNF epigenetics, stress, and psychosis (Boulle et al, 2011). Chronic stress also interacts with the cannabinoid system to sensitize the effects of cannabinoids and shift cannabinoidmediated control of plasticity from projection neurons to GABAergic cells (Patel et al, 2009;Reich et al, 2013).…”
Section: Environmental Insults Disrupt Gabaergic System Developmentmentioning
confidence: 68%
“…In rodents, differential production of Bdnf splice variants has been documented in a number of models of neurological and neuropsychiatric disease and in response to various pharmacological treatments (Dias et al, 2003;Fumagalli et al, 2012;Nair et al, 2007;Zuccato et al, 2001). In humans, misregulation of specific BDNF transcripts is associated with several brain disorders, including Huntington's disease, schizophrenia and Alzheimer's disease (Garzon et al, 2002;Wong et al, 2010;Zuccato et al, 2001). Moreover, a selective deletion of BDNF exons I-III that spares the remaining portion of the gene is sufficient to cause obesity in humans (Han et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Chen et al (2001) showed that there was no significant variation for mBDNF among patients with schizophrenia and those with a diagnosis of affective disorders (unipolar and bipolar disorders) and Dunham et al, (2009) detected no difference for preproBDNF (35KDa) between patients with schizophrenia and those with unipolar depression and bipolar disorder. In contrast, Wong et al (2010) found reduced truncated BDNF and preproBDNF proteins in the DLPFC of patients with schizophrenia, even if the reduction in preproBDNF protein did not achieve statistical significance. In a previous study (Carlino et al, 2011), we provided evidence of variation in serum levels of different BDNF isoforms in patients with chronic schizophrenia.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 57%
“…Reduced mBDNF levels were found in three studies (Karege et al, 2005;Weickert et al, 2003;Wong et al, 2010), particularly in the dorsolateral prefrontal cortex (DLPFC) of patients with schizophrenia compared to healthy controls. Weickert et al (2003) found that mBDNF protein levels were not associated with post-mortem interval (PMI), tissue pH, age, or storage time of the serum.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 99%